Options available for improved forage production under highland conditions. The Pakistan experience - Dost M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The forage production and availability were affected by single cut vs. multi-cut, hybrid vs. varieties, legumes vs. cereal crops, sole cropping vs. intercropping, altering planting dates, different types and doses of chemical fertilizer. Non winter dormant/ improved alfalfa and Egyptian clover varieties were 2-3 times more productive than the local landraces commonly cultivated in the region. The improved forage production techniques also provided forage during the deficit periods. Improving the performance of the high-altitude summer pastures being difficult and time-consuming task and would not alleviate the winter forage scarcity problem. Main emphasis should therefore, be put on improving fodder production and conservation on the agricultural holdings. Since holding size is minute, the aim must be to maximize production per unit of area. Fodder production in these isolated, high areas had been little studied. The population has had no easy access to the technology and seed supplies available in the plains and, for the higher areas, technology from lower down is not appropriate.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)